AUTHORITY, TEXTS AND EDUCATIONAL MODELS: ‎ TRACKING RELIGIOUS MODERATION IN THE ‎TRADITIONAL ISLAMIC EDUCATION OF PESANTREN - Rofikasari Mutmainah; Mohammad Asrori; M. Mujab (SOSIOEDUKASI, 2025)
This article examines the practice of religious moderation within the pesantren tradition through ‎a descriptive-analytical literature review approach. Departing from the assumption that ‎pesantren are not only traditional Islamic educational institutions but also key centers of ‎religious discourse production and ethical formation, this study investigates how values such as ‎tolerance, non-violence, and the acceptance of diversity are transmitted and institutionalized ‎within the epistemic structure and social praxis of pesantren. The analysis focuses on three core ‎aspects: the role of the kiai’s authority in shaping religious interpretive horizons; the dynamics of ‎pedagogy that cultivate tolerance through dialogical methods and communal interaction; and the ‎dialectics between the state’s narrative of religious moderation and the pesantren’s localized ‎practices. The article argues that the success of religious moderation in pesantren largely ‎depends on the kiai’s ability to exercise epistemic authority in a reflective and inclusive manner, ‎as well as on the pesantren’s capacity to internalize tolerance through lived educational ‎experiences and interpretive traditions. Meanwhile, state-driven narratives of moderation will ‎only be effective if implemented through dialogical partnerships rather than top-down ‎bureaucratic interventions. By positioning moderation as a living and adaptive interpretive ‎culture, the article highlights the strategic potential of pesantren as agents of peaceful, context-‎sensitive, and socially relevant Islamic religiosity in plural societies.‎